How to maintain home nutrition therapy after recovery from COVID-19 - Luciana Budiati Sutanto (World Nutrition Journal, 2020)
Survivor patients need enough calories and protein to replace their body weight and protein lost during hospitalized. Especially for COVID-19 patients who were admitted to the ICU often longer than ordinary pneumonia cases, up to 2-3 weeks, followed by severe weight lost.